Design and characterization of zirconia nanoparticles filled polydimethylsiloxane composites based flexible capacitance pressure sensor - Soly Mathew; Krishnamoorthi Chintagumpala (Sensors International, 2025)
Flexible capacitance pressure sensors (fCPS) are widely researched due to their compact geometry and low power consumption, wireless sensor output readability. fCPS show sensitivity by either change in dielectric permittivity (ϵ) or dimension (strain) of dielectric sandwich layer in parallel plate capacitor (PPC) configuration. In addition, fCPS should have low dielectric loss, low driving electric field. All these can be easily achieved with high dielectric constant fillers in flexible elastomers. Here zirconia nanoparticles (ZNPs) at 0, 0.5, 1, & 1.5 wt% were dispersed in polydimethylsiloxane (PDMS) matrix to fabricate four different dielectric elastomer composites (DEC) sandwich layers for fCPS. fCPS were made by sandwiching the DECs between flexible polyethylene terephthalate (PET) substrates coated with conductive silver epoxy. Both dielectric constant and sensitivity increases with ZNPs filler content. Out of four fCPS fabricated, the sensor with 1.5 wt% ZNPs DEC sandwich layer shows very high sensitivity of 1.69 kPa−1 in 0–5 kPa range, and shows low sensitivity (0.006 kPa−1) in 5 – 145 kPa. This fCPS was also shown small hysteresis (5.4%), fast response and recovery time (128 & 190 ms), and long durability. The sensor data were compared and contrasted with the literature data. Touch, motion, and strain sensing capabilities of this fCPS were also studied. It shows very good functionalities of the above functions. Thus it shows good prospectus for both biomedical (vital sign monitor, gait analysis, communication), and industrial (robotic, human machine interface) applications.